1995
DOI: 10.1111/j.1365-2389.1995.tb01342.x
|View full text |Cite
|
Sign up to set email alerts
|

Radio‐caesium fixation dynamics: measurement in six Cumbrian soils

Abstract: Five peat soils and a mineral soil were artificially contaminated with 137Cs. Soil solution activity and radio-lability of 137Cs were monitored over 709 days to quantify progressive 137Cs fixation. The peat soils fixed large amounts of 137Cs, but less than the mineral soil did. Distribution coefficients (&, cm3 g-') ranged from 30 to 5000 at the end of equilibration. A labile 137Cs distribution coefficient, Kdlr was estimated by a method involving solid e solution equilibration in dilute solution.In a separate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 27 publications
(24 reference statements)
3
62
0
Order By: Relevance
“…The amount of rapidly desorbed radiocaesium decreases with the adsorption time, in accordance with earlier observations of a progressively stronger binding between Cs and illite with increasing reaction time (e.g., Mundschenk, 1983;Comans et al, 1991;Absalom et al, 1995). The slow rate of desorption, operationally defined as the desorption occurring after more than 24 h desorption time, was interpreted in terms of a first order process.…”
Section: Radiocaesium Sorption and Desorption On K- Na- And Nh 4 -Isupporting
confidence: 61%
See 1 more Smart Citation
“…The amount of rapidly desorbed radiocaesium decreases with the adsorption time, in accordance with earlier observations of a progressively stronger binding between Cs and illite with increasing reaction time (e.g., Mundschenk, 1983;Comans et al, 1991;Absalom et al, 1995). The slow rate of desorption, operationally defined as the desorption occurring after more than 24 h desorption time, was interpreted in terms of a first order process.…”
Section: Radiocaesium Sorption and Desorption On K- Na- And Nh 4 -Isupporting
confidence: 61%
“…The first is that the frayed edge site structure of the clay minerals collapses under the influence of high concentrations of adsorbed alkali metal ions, thus preventing the further release of radiocaesium (Madruga, 1993;Absalom et al, 1995;Absalom et al, 1996). Alternatively, Sparks (1989) argued that when the ion-exchange method is used in a batch procedure, a relatively high concentration of the desorbed species (i.e., 137 Cs) builds up in solution, which could inhibit further adsorbate release from the solids.…”
Section: Radiocaesium Sorption and Desorption On K- Na- And Nh 4 -Imentioning
confidence: 99%
“…The exchangeability did not change substantially over the experimental period; however, statistical analysis did suggest that the exchangeability observed after harvest was significantly lower than that before harvest due mainly to plant uptake (Table 3). Rapid fixation of Cs + by soil has also been suggested by some laboratory studies [15,16] which demonstrated that fixation reached equilibrium less than 30 days after contamination. …”
Section: Extractability Of Cs In Soilmentioning
confidence: 87%
“…However, irrespective of the soil type, the total cesium content within the soil particle size fractions was more or less even and was in the range of 40 to 48 mg kg -1 (Figure 1). This pseudo-uniformity in the cesium distribution in the soil particle size fractions can be attributed to the shorter time-lag between the exposure period and concentration measurements [35]. The particle size can contribute to several effects when 137 Cs is used to estimate soil erosion rates.…”
Section: Effects Of Soil Type and Soil Particle Size On The Cs Assimimentioning
confidence: 99%